2009
DOI: 10.1091/mbc.e09-06-0477
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Poly(ADP-ribose) and NuMA Contributes to Mitotic Spindle Pole Assembly

Abstract: Poly(ADP-ribose) (pADPr), made by PARP-5a/tankyrase-1, localizes to the poles of mitotic spindles and is required for bipolar spindle assembly, but its molecular function in the spindle is poorly understood. To investigate this, we localized pADPr at spindle poles by immuno-EM. We then developed a concentrated mitotic lysate system from HeLa cells to probe spindle pole assembly in vitro. Microtubule asters assembled in response to centrosomes and Ran-GTP in this system. Magnetic beads coated with pADPr, extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 41 publications
(56 reference statements)
5
83
0
Order By: Relevance
“…Interestingly, PARsylation of NuMA by TNKS1 seems to influence the structural integrity of spindle poles and may be essential for protein interactions required for spindle formation. [21][22][23] Together, these findings indicate that TNKS1 might be an essential enzyme responsible for providing poly(ADP-ribose) to the spindle assembly during mitosis and regulating mitotic cell-cycle progression.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, PARsylation of NuMA by TNKS1 seems to influence the structural integrity of spindle poles and may be essential for protein interactions required for spindle formation. [21][22][23] Together, these findings indicate that TNKS1 might be an essential enzyme responsible for providing poly(ADP-ribose) to the spindle assembly during mitosis and regulating mitotic cell-cycle progression.…”
mentioning
confidence: 85%
“…Recent work has also indicated that poly(ADP-ribose) appears to be a key component of mitotic spindle assembly and structure. 8,21 TNKS1 colocalizes with the nuclear mitotic apparatus (NuMA) protein at the spindle poles during mitosis. 22 Localization of TNKS1 at the spindle pole is dependent on the NuMA protein.…”
mentioning
confidence: 99%
“…While some ARTDs modify substrates by transferring iteratively multiple ADP-ribose units resulting in poly-ADP-ribosylation (PARylation), most ARTDs mono-ADP-ribosylate (MARylate) their substrates (Kleine et al, 2008). ARTDs function in DNA damage repair (Malanga and Althaus, 2005;Nicolae et al, 2014Nicolae et al, , 2015, the unfolded protein response (Jwa and Chang, 2012), apoptosis Koh et al, 2005), heat shock (Petesch and Lis, 2008), cellular signaling (Feijs et al, 2013a;, cell division (Chang et al, 2004(Chang et al, , 2005(Chang et al, , 2009Ha et al, 2012), as well as transcription and chromatin regulation Schreiber et al, 2006). PARylating ARTDs (pARTDs; ARTD1-6), most prominently ARTD1, have been the focus of cancer related research during the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to regulating telomerase activity and telomere length, tankyrases work with PARP-3 in the maintenance of telomere integrity [25]. Tankyrase-1 has been found to be active in the process of mitotic spindle pole assembly, during which automodification of tankyrase-1 gathers additional proteins through high affinity binding to the cloud of PAR [27]. Again, niacin deficiency could induce various forms of genomic instability through decreased tankyrase activities, and this remains uncharacterized.…”
Section: Roles Of Alternate Parps In Genomic Stabilitymentioning
confidence: 99%